Synthesis and evaluation of certain diaryl substituted heterocyclic compounds as potential anticancer agents - Soha Hussein Emam Mabrouk; Eman Mohamed Ahmed; Nadia Abdalla Khalil; Salwa Elsayed Mohamed Elmeligie (Cairo : Soha Hussein Emam Mabrouk, 2016)
This thesis comprises five chapters. The first one is an introduction which includes a brief literature survey on the synthesis, anticancer and antimitotic activities of 2-pyrazolines, 1,3,4-oxadiazoles and pyridines. The second chapter clarifies the aim of the work and the schemes adopted for the preparation of the target compounds. The third chapter deals with the theoretical discussion of the experimental work. The fourth chapter consists of the experimental part of the thesis which contains detailed procedures used for the synthesis of the target compounds, as well as the physical properties and detailed data obtained from elemental and spectral analyses. The fifth chapter includes discussion of the anticancer results compared to standard antimitotic agent colchicine, as well as a brief account on the results of the docking study and the correlation between these results and anticancer activity. It also includes the procedures of anticancer testing as well as the docking steps followed
Thesis (Ph.D.) - Cairo University - Faculty of Pharmacy - Department of Organic Chemistry
Issued also as CD
Keywords: 1, 3, 4-oxadiazole; 2-pyrazoline; Pyridine